A Pragmatic Study of Politeness Maxims in the Movie “Kung Fu Panda 4” - Ni Luh Sudiantari; I Gusti Ayu Agung Sintha Satwika (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study analyzes the application of the Generosity and Approbation Maxims in the animated film Kung Fu Panda 4, based on Leech’s (1983) theory and Holmes’s (1992) framework on social factors influencing their use. Using a descriptive qualitative method, nine utterances from the main characters were analyzed through non-participant observation and note-taking. The findings reveal that both maxims are expressed through self-sacrifice, offering help, and praising others, which strengthen interpersonal relationships, demonstrate solidarity, and reflect each character’s personality. The study highlights the crucial role of politeness in maintaining positive communication within animated films.